2014
DOI: 10.1186/1471-2407-14-403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of transient interruption of antiangiogenic treatment using ultrasound-based techniques in a murine model of hepatocellular carcinoma

Abstract: BackgroundDevelopment of escape pathways from antiangiogenic treatments was reported to be associated with enhanced tumor aggressiveness and rebound effect was suggested after treatment stop. Aim of the study was to evaluate tumor response simulating different conditions of administration of antiangiogenic treatment (transient or definitive treatment stop) in a mouse model of hepatocellular carcinoma.MethodsSubcutaneous tumors were created by inoculating 5×106 Huh7 cells into the right flank of 14 nude mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The optimal timing of sorafenib discontinuation remains under debate. [ 30 32 ] In a mouse model evaluating the impact of sorafenib discontinuation, [ 33 ] it was found that transient sorafenib interruption did not impede restoration of tumor response, but definitive sorafenib interruption tended to stimulate a rebound in angiogenesis to a higher level than if sorafenib treatment had never been given. In a retrospective cohort study of patients with advanced HCC, [ 31 ] where even radiologic PD had been confirmed, continuing with sorafenib therapy improved patient survival compared with sorafenib discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal timing of sorafenib discontinuation remains under debate. [ 30 32 ] In a mouse model evaluating the impact of sorafenib discontinuation, [ 33 ] it was found that transient sorafenib interruption did not impede restoration of tumor response, but definitive sorafenib interruption tended to stimulate a rebound in angiogenesis to a higher level than if sorafenib treatment had never been given. In a retrospective cohort study of patients with advanced HCC, [ 31 ] where even radiologic PD had been confirmed, continuing with sorafenib therapy improved patient survival compared with sorafenib discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…BR55, a VEGFR2-specific ultrasound contrast agent, was developed with a similar method and quickly entered clinical trials since its first publication . Numerous studies have reported the usefulness of BR55 as an ultrasound molecular probe in detecting early-stage tumors or liver dysplasia (Bzyl et al 2013;Grouls et al 2013;Sugimoto et al 2012;Tardy et al 2010), in functional diagnosis of differently aggressive breast cancers (Bzyl et al 2011) and in monitoring or evaluating anti-angiogenic cancer therapy (Marinelli et al 2014;Pysz et al 2010). The RGD peptides and mimics can be used to probe integrin functions in various biological systems.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported its specificity and capacity to assess VEGFR2 expression in vivo (BaronToaldo et al 2015;Marinelli et al 2014;Pochon et al 2010;Tardy et al 2010;Willmann et al 2008), as well as its ability to monitor anti-angiogenic treatments (BaronToaldo et al 2015;Marinelli et al 2014;Pysz et al 2010). Marinelli et al (2014) and BaronToaldo et al (2015) monitored sorafenib therapy in hepatocelular carcinoma models using BR55 and detected early changes in VEGFR2 expression. Pysz et al (2010) reported detection of the anti-VEGFR2 antibody blockade using BR55 in a human colon cancer xenograft model in mice.…”
Section: Introductionmentioning
confidence: 98%